Causes of America's Lagging Life Expectancy: An International Comparative Perspective. (21st February 2022) - Ho, Jessica Y
Abstract: Objectives: This study assesses how American life expectancy compares to other high-income countries and identifies key age groups and causes of death responsible for the U.S. life expectancy shortfall. Methods: Data from the Human Mortality Database, World Health Organization Mortality Database, and vital statistics agencies for 18 high-income countries are used to examine trends in U.S. life expectancy gaps and how American age-specific death rates compare to other countries. Decomposition is used to estimate the contribution of 19 age groups and 16 causes to the U.S. life expectancy shortfall. Results: In 2018, life expectancy for American men and women was 5.18 and 5.82 years lower than the world leaders and 3.60 and 3.48 years lower than the average of the comparison countries. Americans aged 25–29 experience death rates nearly 3 times higher than their counterparts. Together, injuries (drug overdose, firearm-related deaths, motor vehicle accidents, homicide), circulatory diseases, and mental disorders/nervous system diseases (including Alzheimer's disease) account for 86% and 67% of American men's and women's life expectancy shortfall, respectively. Discussion: American life expectancy has fallen far behind its peer countries. The U.S.'s worsening mortality at the prime adult ages and eroding old-age mortality advantage drive its deteriorating performance in international comparisons.